The Meaning of Riyadhoh Matang Puluh for Students in Salaf Islamic Boarding School - Jani Khoerani; Suryanto Suryanto (Program Pascasarjana Universitas Ibrahimy, 2024)
Riyadhoh matang puluh is a tradition practiced by students in salaf Islamic boarding schools. The implementation of riyadhoh matang puluh is crucial as an act of inner effort in the process of acquiring knowledge at islamic boarding school. This study aims to understand the practice of riyadhoh matang puluh and explore the meaning of the experience for students at salaf Islamic boarding schools. The participants in this study were two students who had undergone riyadhoh matang puluh. A qualitative method with a phenomenological approach was used. Data collection was conducted through semi-structured interviews. The results of this study indicate that the meaning of riyadhoh matang puluh for the participants is a spiritual exercise to control desires and purify oneself from elements that can taint the soul through activities such as reading the Qur'an and fasting for 41 days. Riyadhoh matang puluh positively impacts self-regulation, and self-control, and enhances religiosity.